What about the Baby? Infancy and Parenting in the COVID-19 Pandemic. Issue 1 (31st December 2022) - Ribaudo, Julie
ABSTRACT: This article reviews the evolution of a newborn through the first year of life and the potential impacts of COVID-19 on the infant, parent, and the parent-infant relationship. Babies grow in the context of relationships, and the quality of those relationships affects the physiological and psychological organization of the baby. Precisely because each baby is a being with unique biology, temperament, and ways of experiencing, feeling, and learning, much is to be discovered and understood about them. The baby's wordless communications require their parents to intuit, infer, hypothesize, and experiment as parents come to know the needs of their baby. As we walk alongside parents who struggle to come to know their infant – even as the infant is coming to know them – we are required to have conceptual knowledge of how a newborn becomes a fully awakened infant. Under typical conditions, the birth of a firstborn baby presents a caregiving challenge and developmental opportunity for the emerging parent. Environmental context can serve to support or interfere in the success of the adjustment. This paper will explore some theoretical underpinnings that contribute to infant and parent well-being and the possible impact of being born during the COVID-19 pandemic. Also considered will be the undue burden of families bearing the weight of economic inequities, oppression, and structurally supported racism. This article will explore the influence of parental perception, the development of attachment relationships, and how that is influenced by and influences infant communication. Finally, it will suggest ways that psychotherapists seeing individuals who are parents can hold the infant in mind as they work to understand and respond to their adult clients navigating the impacts of this pandemic.